ผลของการยิงด้วยลำไอออนและกระบวนการทางความร้อนต่อโครงสร้างผลึกและสมบัติเชิงแสงของพลอยดิบสปิเนล - พานทอง ชนาภา; ไชยนอก กิตติพงศ์; เชิดหิรัญกร เบญญา; บุตรกูล ดวงแข; อินทรศิริ เสวต (Thai Journal of Science and Technology, 2021)
The effects of ion implantation and heat treatment on the crystal structure of natural spinel gemstone (MgAl2O4) were studied. The samples were implanted by nitrogen ions with the fluence of 1 x 1017, 5 x 1017, 1 x 1018 and 5 x 1018 ion/cm2. The single crystal X-ray diffraction analysis at room temperature (296 K) revealed that the un-implanted natural spinel crystallizes in the cubic symmetry with space group F-43m. Whereas no crystallographic phase change is observed for the implanted spinel samples, slightly different unit cell parameters (a, b, c, V) between these samples can be found. Spectroscopy of the implanted and un-implanted spinel samples were characterized by spectroscopic techniques via UV-Vis, Raman as well as photoluminescence spectroscopies. The results show just a slight change found in implanted and un-implanted spinel samples as same as heat-treated spinel at 600-1000 °C.